Flexible flower-like MOF of Cu2(trans-1,4-cyclohexanedicarboxylic acid)2 as the electroactive matrix material for label-free and highly sensitive sensing of thrombin - Qiu, Weiwei; Wang, Qingxiang; Yano, Natsumi; Kataoka, Yusuke; Handa, Makoto; Gao, Feng; Tanaka, Hidekazu (Electrochimica Acta, 2020)
A flexible metal-organic framework (MOF) of Cu2(trans-1,4-cyclohexanedicarboxylic acid)2 (Cu2(CHDC)2) has been synthesized by a facile hydrothermal method. The physical characterization experiments show that the Cu2(CHDC)2 presents unique flower-like shape, large surface area and high electroactivity. Then gold nanoparticles (AuNPs)/Cu2(CHDC)2 modified electrode was prepared and utilized as an electroactive matrix for thrombin aptamer immobilization. The electrochemical assay shows that the AuNPs can effectively enhance the electrochemical signal of the Cu2(CHDC)2. Upon the binding of the electrode-confined aptamer with the thrombin, the electrochemical signal of the Cu2(CHDC)2 decreases obviously due to the change of the microenvironment of the sensing interface. Thus a label-free electrochemical sensing strategy for thrombin was realized. The aptasensor displays excellent performance with wide linear range, ultralow detection limit of 0.01 fM (S/N = 3), and favorable specificity. Also, the aptasensor was applied for determination of thrombin in the human serum samples, and the satisfactory results are obtained. The results imply that the proposed sensor can be potentially used for the early diagnosis of disease and clinical monitoring. •A flexible flower-like MOF of Cu2(CHDC)2 was synthesized.•The Cu2(CHDC)2 present high surface area and outstanding electrochemical activity.•The Cu2(CHDC)2 coupled with AuNPs was utilized for construction of signal-off aptasensor.•The aptasensor displays an ultralow detection limit of 0.01 fM and favorable specificity.